Brain death The resuscitator's behaviour - Proietti, Rodolfo; Zanghi, Filippo (Medicina e Morale, 2024)
It should be premised that the fundamental objective of the resuscitator is not to ascertain brain death but to prevent it. To this end, pharmacological and instrumental therapy measures aimed at restoring normal brain function must be taken in all patients with a severe lesion of the Central Nervous System, and thus an elevated risk of brain death.